1982
DOI: 10.1007/bf00349018
|View full text |Cite
|
Sign up to set email alerts
|

Pectinases in leaf degradation by aquatic hyphomycetes I: the field study

Abstract: The colonization-pattern of aquatic Hyphomycetes on five-gram leaf packs of oak and alder submerged in a stream was quantified and compared. There were three series of alder leaves, submerged two weeks apart, and one series of oak. Colonization of leaves by pectolytic bacteria was also measured. There were marked similarities in the colonization of all four series. Total spore counts/g dry wt of leaf rose to a peak followed by a decline. The time taken to peak colonization was slower in oak than in alder, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Evidence for substrate specificity among aquatic hyphomycetes has been presented by Gonczol (1975Gonczol ( , 1989, Sridhar and Kaveriappa (1988) and, to a lesser extent, Chamier and Dixon (1982), and Bengtsson (1983) has demonstrated habitat (substrate) selection in two species of aquatic hyphomycetes. However, in a New Zealand study, Aimer and Segedin (1985) claimed to have found no evidence of substrate specificity, and Gonczol (1987) suggested that some of the specificity detected in his 1975 study had perhaps been more closely related to changes in stream-water chemistry than to leaf type.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evidence for substrate specificity among aquatic hyphomycetes has been presented by Gonczol (1975Gonczol ( , 1989, Sridhar and Kaveriappa (1988) and, to a lesser extent, Chamier and Dixon (1982), and Bengtsson (1983) has demonstrated habitat (substrate) selection in two species of aquatic hyphomycetes. However, in a New Zealand study, Aimer and Segedin (1985) claimed to have found no evidence of substrate specificity, and Gonczol (1987) suggested that some of the specificity detected in his 1975 study had perhaps been more closely related to changes in stream-water chemistry than to leaf type.…”
Section: Introductionmentioning
confidence: 97%
“…However, in a New Zealand study, Aimer and Segedin (1985) claimed to have found no evidence of substrate specificity, and Gonczol (1987) suggested that some of the specificity detected in his 1975 study had perhaps been more closely related to changes in stream-water chemistry than to leaf type. The fungal communities of most substrates studied have been found to be dominated by 5 to 10 abundant to moderately common species of aquatic hyphomycetes, although not all substrates are dominated by the same species (Iqbal et al 1979;Sanders and Anderson 1979;Chamier and Dixon 1982;Chamier et al 1984). Chamier and Dixon (1982) and Sridhar and Kaveriappa (1988) suggested that substrate preferences may be more common among aquatic hyphomycetes than substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, more than 90% of all spores are produced by one to four species (6). There is some evidence of successional trends (9,20). These changes may be in response to seasonal changes in temperature (32, 42), or rare species might arrive late during the decay of a substrate (2).…”
mentioning
confidence: 99%
“…Maystrenko et at., 1969;Olah, 1972;lJlehlovli, 1976;Morrison et al, 1977;Chamier & Dixon, 1982;Federle & Vestal, 1982). Bacteria are typically first to colonize, and their numbers increase rapidly after a few days.…”
Section: Decomposer Organismsmentioning
confidence: 98%